Continuous Erector Spinae Plane Block for Analgesia after Thoracotomy for Lung Transplantation in an Anticoagulated Patient - Mark Mudarth; Veena Satyapriya; John Coffman; Peter DeSocio; Alec Lawrence; Shana Schwartz; Michael Kushelev (Case Reports in Anesthesiology)
Lung transplant recipients are at particular high risk for postoperative respiratory failure as a result of poorly controlled pain, inadequate graft expansion, decreased cough, and reliance on systemic opioid therapy. Thoracic epidural and paravertebral blocks have been employed with the goal of improving postoperative pain control, improving pulmonary mechanics, and limiting the need for narcotic administration. These approaches require a needle position in proximity to the neuraxis and may cause significant hypotension that is poorly tolerated in transplant patients. Additionally, the use of anticoagulation or underlying clotting disorder limits the use of these regional blocks because of the concern of hematoma and subsequent neurologic injury. Ultrasound-guided continuous erector spinae plane (ESP) block has been shown to be efficacious for pain control following thoracotomy but has had minimal investigations following lung transplantation. In this study, we describe the effective use of a continuous erector spinae plane block to provide analgesia in a postoperative lung transplant recipient receiving systemic anticoagulation. The use of an ESP block with a more superficial needle tract that is further removed from the neuraxis allowed for a greater safety profile while providing efficacious pain control, decreased reliance on systemic narcotics, and improved oxygen saturation. The ESP block was effective in this case and thus may be a valuable alternative following lung transplantation for patients who are not candidates for thoracic epidural or paravertebral approaches.